What Can Economics Say About Procrastination - Fibiger, Ivo; Janíčko, Martin, 1983-; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
The thesis analyzes the measure of academic procrastination among students and the measure of general procrastination among working population with a university degree. The thesis includes 3 studies. In study 1 an experiment was conducted on 33 students of the University of Economics in Prague. The results show, that students achieve better academic results given external, evenly distributed deadlines compared to when they are allowed to set the deadlines themselves. The second study analyses long-term data about 1909 students of the University of Economics and their academic results. The results show that procrastination can influence as much as 8% of the final grade. Study 3 analyzes information about 2487 subjects and their tax-return forms. It puts into context the dates of submission of the tax returns and personal characteristics of the submitters. The results show that procrastination declines with age. Methods on how to fight procrastination are suggested at the end of the thesis.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses